1982
DOI: 10.1063/1.93046
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low threshold (AlGa)As graded-index waveguide separate-confinement heterostructure lasers grown by molecular beam epitaxy

Abstract: Extremely low threshold GRIN-SCH lasers with single and double active layers were prepared by molecular beam epitaxy as a result of an increased optical confinement, a significant reduction in the internal loss αi, and the increased gain constant β. Averaged Jth 250 A/cm2 and 160 A/cm2 for broad-area Fabry–Perot diodes of cavity lengths 380 and 1125 μm, respectively, and averaged external differential quantum efficiency ηD of 65–80 % were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(35 citation statements)
references
References 13 publications
0
33
0
2
Order By: Relevance
“…Because the relative magnitudes of the round-trip time in the cavity r g and the average lifetime of the carriers r encountered in the semiconductors of interest are such that r g r, the derivative (d</>)/(dt) in (14) can be neglected [35]. Likewise, the natural logarithm ln(n/no) in (14) admits a Taylor series expansion around n « m (15) where P s = n$hb>wd/(a\ og Tr) and b = -47rno/(Aaio g )(diV/dn), in the limit when the carrier concentration tends to the transparency carrier density.…”
Section: Sine Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the relative magnitudes of the round-trip time in the cavity r g and the average lifetime of the carriers r encountered in the semiconductors of interest are such that r g r, the derivative (d</>)/(dt) in (14) can be neglected [35]. Likewise, the natural logarithm ln(n/no) in (14) admits a Taylor series expansion around n « m (15) where P s = n$hb>wd/(a\ og Tr) and b = -47rno/(Aaio g )(diV/dn), in the limit when the carrier concentration tends to the transparency carrier density.…”
Section: Sine Functionmentioning
confidence: 99%
“…A logarithmic relation between the optical material gain and the carrier concentration will be employed in the laser model and the results of the analysis will be applied to a quantum-well laser device. As compared with bulk semiconductor materials, quantum wells possess superior characteristics, such as low threshold current [14], [15], low temperature dependence [16], long-wavelength operation [17], and nonlinear effects [18], that justify our choice. Lastly, this analysis will be contrasted with the results of a well-known commercial photonics software tool.…”
Section: Introductionmentioning
confidence: 99%
“…3) The free-carrier distribution in the transverse direction (direction of the structure growth, ) in the OCL is also assumed uniform const (2) This assumption means that the current is far from being controlled by diffusion across the OCL. Although transport to the active layer can affect the dynamic laser response [27], [28], it can be ignored in evaluating the steady-state output power.…”
Section: )mentioning
confidence: 99%
“…We found that the band gap of the heterostructures was extended obviously. Heterostructure engineering is now widely practiced, producing the most efficient semiconductor lasers [9], highest-speed transistors [10], and novel quantum electronic devices [11]. If the nontransmission frequency range (PBG along the incident direction) of the constituents has a proper lineup, this can be essentially enlarged as desired by using different PCs to form photonic multiple heterostructures.…”
Section: Introductionmentioning
confidence: 99%